Smoothing Consumption by Smoothing Income: Hours-of-Work Responses to Idiosyncratic Agricultural Shocks in Rural India - Kochar, Anjini (The Review of Economics and Statistics, 1999)
While research has demonstrated that farm households in developing economies are able to protect consumption from idiosyncratic crop shocks, little evidence shows how this is achieved. This paper examines the extent to which labor markets allow households to shift labor from farm to off-farm employment, and the extent to which such a shift explains the observed lack of correlation between consumption and idiosyncratic crop shocks. The empirical analysis uses a novel measure of the idiosyncratic crop income shock which utilizes information on start-of-season cropping choices to more accurately estimate household expectations of weather.